Attenuation of P and S Waves in the Javakheti Plateau, Georgia (Sakartvelo) - Ia Shengelia; Nato Jorjiashvili; Tea Godoladze; Irakli Gunia; Dimitri Akubardia (International Journal of Geophysics)
The frequency-dependent parameters of attenuation of P and S waves in one of the most seismically active regions, of the Javakheti plateau, have been estimated using digital data for the first time. We have analyzed and processed hundred and fifty local shallow earthquakes that occurred from 2006 to 2018 and were recorded by five seismic stations. The quality factors for P waves (Qp) and for S waves (Qs) were evaluated by means of the extended coda normalization method. The obtained Qp and Qs are strongly frequency dependent in the frequency range of 1.5 to 24 Hz, and increase with frequency according to the following power laws: QP=17.4±2.3f1.100±0.033 and QS=28.8±3.3f1.048±0.039. The observed Qs/Qp  ratio was found to be greater than unity over the entire frequency range, suggesting that scattering may play the main role in the attenuation of body waves on the Javakheti plateau. The frequency dependence of the S wave is very similar to the frequency dependence of the shear wave for another seismically active region of Georgia, the Racha area. A comparison of our results to those other regions of the world shows that among the seismically active areas, the Javakheti plateau is characterized by relatively low values of Qp and Qs, but they are more than volcanic regions such as Etna and Qeshm Island, Iran. The observed results characterize the entire earth’s crust in the study area and will be useful for source parameter estimation, ground motion prediction, and hazard assessment of the Javakheti plateau.